Dukungan Belajar Multimodal dalam Meningkatkan Keterampilan Siswa pada masa Pandemi Covid-19 di Desa Jati Sari Kecamatan Padang Tualang Kabupaten Langkat - Wawan Arbaini (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2021)
This dedication activity is motivated by the fact that many parents are unable to accompany their children to study from home during the pandemic due to various alibis and jobs. Another obstacle is that students are unable to master lesson modules independently, lack of support for facilities, some students and parents are not able to operate gadgets, moreover there are students who do not have gadgets, thus limiting their exploration of online education. Therefore, this student learning assistance was tried with the aim of increasing students' description, activity, creativity, and self-confidence in education. The procedure for implementing mentoring is carried out in several stages, namely preparation, application of mentoring, and assessment. With the existence of this multimodal education innovation, it has been proven to be very helpful for students who were previously quiet, shy, and unsure of themselves. After exploring this mentoring process, participating students become more active, creative, and have great self-confidence.